VD_FINDINFO Jug / 2021 / 117 vom 20. August 2020 - VD Tribunal cantonal (2020)
ESCROQUERIE, TROMPERIE, ASTUCE, AFFECTIONSENTIMENT, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 146 al. 1 CP, 251 ch. 1 CP, 43 al. 1 CP, 47 CP, 49 al. 1 CP